Physiological Disorders in Orchids: Mesophyll Cell Collapse - Robert A. Cating; Aaron J. Palmateer (EDIS, 2009)
PP265, a 3-page illustrated fact sheet by R. A. Cating and A. J. Palmateer, describes this physiological disorder that affects many genera of orchids and can be caused by exposure to low water temperatures or low air temperatures. Includes references. Published by the UF Department of Plant Pathology, May 2009.